1975
DOI: 10.1111/j.1469-8137.1975.tb01371.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salt and Osmotic Stress on the Retention of Potassium by Excised Barley and Bean Roots

Abstract: SUMMARYThe effect of different concentrations of NaCl, mannitol and CaCIj on the retention of potassium ion by preloaded roots of barley, Hordeum vulgare, and bean, Phaseolus vulgaris, indicated that 10 mM NaCl had no effect on potassium loss, but 50 mM NaCl or more increased the rate of efflux. Barley roots appeared 10 be more sensitive to salt stress than bean roots since 100 mM NaCl caused 78% potassium loss over 6.5 h by barley as compared with 40% loss by bean roots. Mannitol up to 200 mM had no eifect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
3
14
1
Order By: Relevance
“…Consistent with studies on other plant species ( e.g. , barley [12], [20], wheat [23], bean [54], cotton [16], Arabidopsis [13], pea [55], alfalfa [56], and sunflower (our unpublished results)), we show that sudden exposure to high levels of NaCl produce a significant and sustained stimulation of K + efflux in three cultivars of rice that differ dramatically in salt tolerance. We also show that this effect occurs regardless of nutritional history (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with studies on other plant species ( e.g. , barley [12], [20], wheat [23], bean [54], cotton [16], Arabidopsis [13], pea [55], alfalfa [56], and sunflower (our unpublished results)), we show that sudden exposure to high levels of NaCl produce a significant and sustained stimulation of K + efflux in three cultivars of rice that differ dramatically in salt tolerance. We also show that this effect occurs regardless of nutritional history (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In roots of the saltsensitive P. media, salinity caused a strong decrease in the levels of phospho-, galacto-, and sulfolipids, indicating decreased control of permeability of rootcell membranes. Nassery (1975) showed that salt-induced potassium leakage from barley and bean roots is not the result of osmotic effects. Sodium chloride can cause potassium leakage from plant roots (Nassery, 1975(Nassery, , 1979Bates, 1976).…”
Section: Ion Toxicitymentioning
confidence: 99%
“…1a). Upon sudden, "shock", applications of higher concentrations of Na + , membrane disintegrity due to osmotic shock and ionic displacement (particularly of Ca 2+ ), result in the release of cellular contents, including K + and water (Nassery 1975(Nassery , 1979Lynch and Läuchli 1984;Cramer et al 1985;Britto et al 2010;Coskun et al 2013; Fig. 1b), offering an alternative, or additional, explanation of enhanced K + release under Na + exposure (Britto et al 2010;Coskun et al 2013).…”
Section: Sodium Toxicitymentioning
confidence: 99%
“…Cytsolic concentrations of K + and Na + ([K + ] cyt and [Na + ] cyt , respectively) and resting membrane potentials can alter with long-term Na + stress (Hajibagheri et al 1988;Flowers and Hajibagheri 2001;Carden et al 2003;Kronzucker et al 2006). b Sudden salinity stress can result in membrane disintegrity (osmotic shock) and the release of cellular contents, including K + and water (Nassery 1975;Cramer et al 1985;Britto et al 2010;Coskun et al 2013) K + provision (but not complete deprivation; Evans and Sorger 1966), or when K + uptake is partially inhibited, including by Na + itself (see above, and Figs. 1 and 2), Na + may well "rise to the challenge" of filling in for K + in more than one of its key functions.…”
Section: Sodium As a Nutrientmentioning
confidence: 99%